Evaluation and updates to the Leggett model for pharmacokinetic modeling of exposure to lead in the workplace – Part II adjustments to the adult exposure model, confirmation of Leggett+, and modeling of workplace exposure. - Vork, Kathleen L.; Brown, Joseph P.; Carlisle, James C. (Journal of Occupational & Environmental Hygiene, 2023)
California's Office of Environmental Health Hazard Assessment has updated the comprehensive age-specific model of lead metabolism in humans published by Richard W. Leggett in 1993. The updated model, called Leggett+, was introduced in a peer-reviewed report in 2013. The Leggett + model simulates the relationship between blood lead and exposure in the workplace. Leggett + includes a workplace exposure model comprising respiratory tract intake (workplace lead inhaled by a worker) and uptake (lead absorbed into the blood from the respiratory tract plus uptake from ambient air and diet). The latter is calculated as intake times an inhalation transfer coefficient plus background uptake. An adjusted adult systemic model describes the metabolism of the absorbed lead. This paper provides details about the workplace exposure and uptake elements of Leggett+, an updated approach to calibrating an inhalation transfer coefficient, confirmation of the model's performance in predicting blood lead levels from workplace studies, and predictions of blood lead levels from simulated exposures to workplace airborne lead over a working lifetime. Blood lead relative to airborne lead concentrations in a standard workplace scenario predicted by Leggett + was similar to corresponding relationships from four published workplace studies. Leggett + predictions displayed a good fit to regression equations when other key factors were considered such as pre-employment blood lead and ongoing background intake of lead, workplace air concentration, lead aerosol characteristics, and worker activity levels. The comprehensive Leggett + model can simulate plausible workplace air–blood lead relationships from a broad range of worker exposures. The inhalation transfer coefficient of 0.30, derived from empirical data described in the 2013 report has been reexamined. The original estimate continues to represent a plausible mid-point for a coefficient derived from an expanded range of theoretical particle size distributions deposited in the upper and lower regions of the respiratory tract considering intake during sedentary and outdoor activity breathing scenarios. This coefficient is slightly lower than the value of 0.35 estimated for unknown forms of lead by Leggett in 1993.